2009
DOI: 10.1134/s0006297909050137
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and properties of fungal β-glucosidases

Abstract: Using chromatography on different matrixes, three beta-glucosidases (120, 116, and 70 kDa) were isolated from enzymatic complexes of the mycelial fungi Aspergillus japonicus, Penicillium verruculosum, and Trichoderma reesei, respectively. The enzymes were identified by MALDI-TOF mass-spectrometry. Substrate specificity, kinetic parameters for hydrolysis of specific substrates, ability to catalyze the transglucosidation reaction, dependence of the enzymatic activity on pH and temperature, stability of the enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 13 publications
3
46
0
2
Order By: Relevance
“…HjCel3A Has a Broad Substrate Specificity-It has been shown that HjCel3A is able to hydrolyze cellooligosaccharides of DP2 to DP6 as well as various ␤-linked glucobioses (56). In this study, the kinetic parameters of HjCel3A have been determined in more detail using the chromogenic substrate CNPG, glucosyl disaccharides, and cellooligosaccharides (cellotriose and cellotetraose).…”
Section: Effect Of Hjcel3a On Cellulose Degradation By Cellulasementioning
confidence: 99%
“…HjCel3A Has a Broad Substrate Specificity-It has been shown that HjCel3A is able to hydrolyze cellooligosaccharides of DP2 to DP6 as well as various ␤-linked glucobioses (56). In this study, the kinetic parameters of HjCel3A have been determined in more detail using the chromogenic substrate CNPG, glucosyl disaccharides, and cellooligosaccharides (cellotriose and cellotetraose).…”
Section: Effect Of Hjcel3a On Cellulose Degradation By Cellulasementioning
confidence: 99%
“…The same pattern was registered in this study, indicating a greater saccharification of cellulose by A. japonicus. The characteristics of the β-glucosidase produced by A. japonicus have been previously assessed for a potential use in biomass saccharification (Korotkova et al 2009). Pasin et al (2014) reported high levels of amylase activity in A. japonicus when cultivated in different agro-industrial residues.…”
Section: Enzymesmentioning
confidence: 99%
“…In addition, the ␤-glucosidase activity can synergistically optimize the action of other cellulolytic enzymes, increasing the yield of the final product and decreasing the concentration of cellobiose, which is a strong inhibitor of the cellulolytic complex, especially of cello-biohydrolases, in the reaction mixture (2). Commercially available cellulase preparations are often supplemented with fungal ␤-D-glucosidases to increase the cellulolytic efficiency on pretreated biomass (3).…”
mentioning
confidence: 99%
“…Six of the enzymes are from bacteria as follows: ␤-N-acetylhexosaminidase from Vibrio cholerae (NagZ), PDB 2 code 1TR9 3 ; exo-1,3-1,4-␤-glucanase (ExoP) from Pseudoalteromonas sp. BB1, PDB code 3F93 (7); ␤-N-acetylglucosaminidase (StNagZ) from Salmonella typhimurium, PDB code 4GVF (8); macrolide ␤-glycosidase/␤-glucosidase (SvDesR) from Streptomyces venezuelae, PDB code 4I3G (9); ␤-N-acetylglucosaminidase from Bacillus subtilis (YbbD), PDB code 3BMX (10); and a ␤-glucosidase from Thermotoga neapolitana (TnBgl3B), PDB code 2X40 (11); four are eukaryotic enzymes, exo-␤-1,3-1,4-glucanase (ExoI) from Hordeum vulgare subsp.…”
mentioning
confidence: 99%